Neoadjuvant radiotherapy plus single-incision thoracoscopic surgery in the treatment of type B3 thymomas - Li, Wenshan; Wu, Yimin; Huang, Lijian; Chai, Ying (Frontiers in Oncology, 2023)
Background Although minimally invasive surgery is the standard treatment for thymomas, minimally invasive thymectomy is difficult for patients with type B3 thymomas, especially for giant or aggressive lesions. These tumors are frequently treated with radical radiation therapy or surgery plus adjuvant radiotherapy. Few studies, however, have tested the efficacy of neoadjuvant radiotherapy prior to thoracoscopic surgery. Methods Patients with type B3 thymomas >5 cm or with infiltrates into vital organs on CT-guided puncture biopsy who underwent neoadjuvant radiotherapy followed by single-incision minimally invasive thymectomy from March 2016 to July 2020 were retrospectively evaluated. Reduction ratios, TNM stage changes according to WHO stage criteria, resectability, long-term survival, and the response in terms of RECIST v1.1 criteria achieved by preoperative RT were analyzed. Results The 11 patients who underwent neoadjuvant radiotherapy plus minimally invasive thymectomy included five men and six women, of mean age 49.5 years. Four patients had myasthenia gravis. Neoadjuvant radiotherapy consisted of 50 Gy in 25 fractions, with all patients showing varying degrees of lesion reduction after radiotherapy. Surgery was performed about 1 month after neoadjuvant radiotherapy, with none of these patients having severe radiation pneumonitis. All patients underwent radical resection of the tumor and adjacent tissue, with none experiencing tumor seeding or rupture during surgery. The median postoperative hospital stay was 3 days (range: 2–6 days) and the frequency of additional regular analgesics (including those for wound pain and neuralgia) was 2.5 times per person. On follow-up, one patient experienced pleural metastasis and one experienced pulmonary metastasis, with the other nine patients showing no evidence of tumor recurrence. Conclusion Neoadjuvant radiotherapy followed by minimally invasive surgery was a safe and efficacious procedure for the treatment of type B3 thymomas, with less postoperative pain and faster recovery. This strategy, of tumor shrinkage prior to surgery, may make possible the easier removal of type B3 thymomas by single-incision thoracoscopy.